Komunikasi Profetik dalam Sosialisasi Mencegah Penyebaran COVID-19 - Sarjo Haryono (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
The spread of Covid-19 in Indonesia remains high to this day. The government has made various efforts to reduce and control its spread, including through religious preaching. This study aims to examine the forms of Covid-19 prevention socialization through preaching, referred to as prophetic communication. The subjects of this study are news reports on Covid-19 prevention activities using prophetic communication, both from mainstream media and verified social media during the pandemic. The research method used is descriptive analysis, systematically and accurately describing the facts. The results show that many parties, especially religious scholars, have conducted socialization through various forms and materials. However, public awareness to follow prevention guidelines is still lacking. Therefore, broader and well-coordinated dissemination of preaching is necessary to achieve better outcomes.